The Other Air Force : U.S. Efforts to Reshape Middle Eastern Media Since 9/11 - Sienkiewicz, Matt (Book collections on Project MUSE., 2016)
As it seeks to win the hearts and minds of the Muslim world, the United States has poured millions of dollars into local television and radio programming. However, as this fascinating new book shows, the Middle Eastern media producers who rely on these funds are hardly puppets on an American string, but instead contribute their own political and artistic agendas. The Other Air Force reveals the remarkable creative output that can emerge even from the world's tensest conflict zones.